The non-Siphonophoran Hydrozoa (Cnidaria) of Salento, Italy with notes on their life-cycles: an illustrated guide - Gravili, Cinzia; Vito, Doris De; Camillo, Cristina Gioia Di; Martell, Luis; Piraino, Stefano; Boero, Ferdinando (Zootaxa, 2015)
The majority of Hydrozoa is represented by not readily noticeable, small species. In recent decades, however, taxonomic knowledge of the group has increased worldwide, with a significant number of investigations focused on the Mediterranean Sea. Over more than two decades, 115 species of hydrozoans were recorded from coastal waters along nearly 300 km of the Salento Peninsula (Apulia, Italy). For each species, records from different collections were merged into single sheets of a general database. For each species, the following information is reported: description, cnidome, biology, occurrence in Salento, worldwide distribution, and bibliography. Descriptions refer to the benthic hydroid stage and, when present, also to the planktonic medusa stage. The 115 species of Hydrozoa, recorded along the Salento coastline, represent 25% of the Mediterranean Hydrozoa fauna (totaling 461 species), and nearly 3% of 3,702 world’s known species covered in a recent monograph. Four species are non-indigenous, three of them with invasive behavior (Clytia hummelincki, Clytia linearis, and Eudendrium carneum), and one species now very common (Eudendrium merulum) in Salento. The complete life cycle of Clytia paulensis (Vanhöffen, 1910) is described for the first time.